2016
DOI: 10.1111/1556-4029.13390
|View full text |Cite
|
Sign up to set email alerts
|

Scoring of Decomposition: A Proposed Amendment to the Method When Using a Pig Model for Human Studies

Abstract: Decomposition studies often use pigs as proxies for human cadavers. However, differences in decomposition sequences/rates relative to humans have not been scientifically examined. Descriptions of five main decomposition stages (humans) were developed and refined by Galloway and later by Megyesi. However, whether these changes/processes are alike in pigs is unclear. Any differences can have significant effects when pig models are used for human PMI estimation. This study compared human decomposition models to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 27 publications
5
98
2
Order By: Relevance
“…Today, pigs are largely accepted as a reasonable model in forensic sciences and are frequently used for decomposition studies due to their similar physical and biochemical preconditions to humans [37,39]. Although some variations to human decomposition have been reported [11,40], pigs generally depict similar morphological changes [41]. This is also supported by the results of this study.…”
Section: Discussionsupporting
confidence: 84%
“…Today, pigs are largely accepted as a reasonable model in forensic sciences and are frequently used for decomposition studies due to their similar physical and biochemical preconditions to humans [37,39]. Although some variations to human decomposition have been reported [11,40], pigs generally depict similar morphological changes [41]. This is also supported by the results of this study.…”
Section: Discussionsupporting
confidence: 84%
“…Use of consistent methods of evaluation is needed in order for research data to be comparable to other studies and must be accurately applied to all specimens. Keough et al have proposed a modification of the TBS system for pigs in South African environments, but currently, there is no such modification available for rabbits. It should also be noted that the differences in decomposition rate observed in rabbits cannot be simply attributed to the fact that the rabbits were caged while the pig and humans were not.…”
Section: Discussionmentioning
confidence: 99%
“…Limited scoring options may reduce or eliminate the resolution necessary to highlight divergence in gross change. Keogh et al used the Megyesi et al TBS to define the typical trajectory of human decomposition and compared this to observations made within a sample of 20 pig carrion. The authors concluded that the gross changes observed between the two groups were sufficiently different to warrant a separate scoring system for pig carrion.…”
Section: Discussionmentioning
confidence: 99%
“…The initial samples of pigs appear more homogenous and humans more varied, but the pigs tend to have a greater coefficient of variation (Table , Figs ), particularly after a TBS of 25. This may partly be due to the fact that the TBS model was created for humans and does not work as well with pigs . Furthermore, while a pig sample may present as “healthy” and homogeneous in gross examination, animals reared for consumption are not subject to regular health assessment and should not be assumed to be homogeneously “healthy” at the time of death.…”
Section: Discussionmentioning
confidence: 99%